Case Report: Summary of multiple CAR-T expansions in anti-BCMA/GPRC5D bispecific CAR-T cell therapy for multiple myeloma - Wei, Liya; Xiao, Xingxian; Jing, Xin; Zheng, Yuwei; Sun, Xiaoyan; Bai, Wei; Li, Manjun; Luo, Min; Xiao, Yang (Frontiers in Immunology, 2025)
Chimeric antigen receptor (CAR) -T cell therapy targeting B-cell maturation antigen (BCMA) has demonstrated significant efficacy and is considered an ideal target for the treatment of relapsed or refractory multiple myeloma (R/R MM). However, due to the unstable or negative expression of BCMA, single-target BCMA CAR-T cell therapy still faces challenges, whereas targeting G protein-coupled receptor C5 family member D (GPRC5D) provides a new therapeutic direction. Clinical studies have shown that CAR-T cell therapy targeting GPRC5D has promising therapeutic potential for R/R MM. Here, this study is a case report on a 61-year-old male R/R MM patient with extramedullary disease (EMD) who participated in a clinical trial of anti-BCMA/GPRC5D bispecific CAR-T cell therapy. Three months after infusion, the patient achieved a very good partial response (VGPR). Although the patient experienced four episodes of CAR-T cell expansion and developed grade 3 cytokine release syndrome (CRS), the symptoms were well controlled, and the treatment demonstrated generally safe. Our report analyzes the reasons for the four CAR-T cell expansions, highlighting the need for close monitoring and laboratory testing during anti-BCMA/GPRC5D bispecific CAR-T cell therapy. Clinical trial registration: This study was registered on ClinicalTrials.gov, number NCT06068400.